Use of Polyethylene Oxide and Hydroxyethyl Starch as Serum Substitute for Cryopreservation of Mouse Testis Cells - Kostina , Ivanna; Pakhomov , Oleksandr (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 296